Exploitation of Oil Resources in Dubai: Economic Impacts and Environmental Concerns - Ariqin Bashir (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2024)
Dubai, a key emirate within the United Arab Emirates (UAE), has undergone rapid transformation due to the exploitation of its substantial oil reserves. This article explores the historical development of Dubai's oil industry, emphasizing its role in the emirate’s economic growth and urbanization. The economic benefits derived from oil revenues are examined alongside the significant environmental impacts, including pollution and habitat destruction. The paper further discusses Dubai’s efforts towards sustainability and diversification of its economy away from hydrocarbons. By analyzing economic data, environmental reports, and sustainability initiatives, this article provides a comprehensive overview of how Dubai’s oil exploitation has shaped its present and future trajectory. The findings underscore the need for a balanced approach to economic development and environmental preservation in the context of a finite natural resource.